Euro-Mediterranean relations after September 11 : international, regional, and domestic dynamics - Jünemann, Annette, 1959- (Frank Cass, 2004)
A comprehensive study of the nexus between democratization and security in the Mediterranean, which are seen as essentially complementary yet threatened by political trends witnessed since the September 2001 attacks.